PERFORMANCE OF THE JOUYBAN-ACREE MODEL FOR CORRELATING THE SOLUBILITY OF INDOMETHACIN AND ETHYLHEXYL TRIAZONE IN ETHYL ACETATE + ETHANOL MIXTURES - RUIDIAZ M., Miller A.; RODRÍGUEZ D., Sylvia J.; NEITA R., Paula C.; CRISTANCHO B., Diana M.; MARTÍNEZ R., Fleming (Vitae, 2010)
This work reports the experimental volumetric properties and also the saturated solubility of indomethacin and ethylhexyl triazine in ethyl acetate + ethanol mixtures at 293.15 to 313.15 K and evaluates the validity of the Jouyban-Acree (J & A) model to correlate the solubility of these compounds in ethyl acetate + ethanol solvent mixtures. The solubility correlation is studied as a function of temperature and cosolvent composition. The J & A model requires only the experimental solubility values in the pure solvents at all the temperatures under study. The calculated values by using both compounds deviate as mean in 30% from experimental solubility values.